Developing an Inuit-Specific Framework for Culturally Relevant Health Indicators Incorporating Gender-Based Analysis - Jessica Guillou; Derek Rasmussen (2012)
At the request of the Bureau of Women’s Health and Gender Analysis (BWHGA) at Health Canada, Pauktuutit Inuit Women of Canada (Pauktuutit) developed a framework for an Inuit-specific culturally relevant gender-based analysis (GBA) of health determinants. The Inuit-specific framework and follow-up health determinants report show that Inuit-specific health data needs to be separated from other data. The framework also proposes a thematic listing of culturally relevant health determinants for Inuit. The framework and health report show some of the gaps in gender-based analysis of Inuit health indicators and determinants that should be addressed. The framework was well received by Inuit in its first trial use in 2008.